Plyometric stress index: A novel method for quantifying plyometric training - Ho, I. M. K.; Wong, T. S.; Yong, J. T. H.; Fang, H. (Science & Sports, 2023)
Aim The level of difficulty of plyometric exercises is currently classified based on a simple system using "low", "moderate" and "high" intensity to describe. However, unclear stress quantification of plyometric drills may lead to a higher injury risk and inappropriate load. Therefore, the current paper presents a novel field base method for strength and conditioning professionals using the Plyometric Stress Index to quantify and estimate the perceived stress for athletes performing various plyometric exercises. Methods A single demonstrator was recruited to illustrate the practical calculation of the Plyometric Stress Index for several common drills including double- and single-leg hurdle jump, countermovement jump, broad jump, 30-cm drop jump, 50-cm depth jump, and box jump. Videos were taken from either front or side view and analyzed with the aid of calibration poles and mobile apps. The stress index for each leg was calculated with the body mass multiplied by the dropping height for the eccentric phase, and also the dropping height for the landing task. The 50-cm depth jump yielded 68.71 units of plyometric stress index and was the most stressful exercise while the second highest was single-leg low hurdle hop yielding 50.68 units. The least stressful drill was a 76-cm box jump with 19.15 units only. Conclusion Although the ranking of the plyometric stress index for selected drills is somewhat different from the traditional intensity described by the National Strength and Conditioning Association, this novel index may allow practitioners to estimate and monitor the stress or training load for producing periodized plyometric training program.